The National Council of Justice (Background in Peru and Comparative Legislation) - Alzamora Valdez, Mario (1972)
This paper focuses on the proposal for the creation of the National Council of Justice, developing the background to the proposal for the creation of this figure and the comparative legislation with respect to similar figures in other countries. In this sense, the author presents the historical development of the process of appointing judges in Peru and reflects on the independence of the judiciary from the other branches of government. He also presents the regulations and institutions created in other countries in order to provide, in the author's terms, an adequate appointment of members of the judiciary.